PERBANDINGAN MODEL PEMELAJARAN DAN AKTIVITAS BELAJAR TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK KELAS X IPA SMA NEGERI 2 MANOKWARI PADA MATERI SISTEM PERIODIK UNSUR - Aprilia Diah Astuti; Christiana Niken Larasati; Apriani Sulu Parubak (Arfak Chem: Chemistry Education Journal, 2019)
Abstract This study aims to determine: (i) significant differences between the use of the Problem Based Learning (PBL) learning model and the cooperative learning type Team Assisted Individualization (TAI) model on cognitive learning outcomes in periodic elements of material systems; (ii) the presence or absence of the influence of learning activities on periodic system elements; (iii) the interaction between learning models for cognitive learning activities and outcomes in periodic system elements. This research is an experimental study with a 2x2 factorial design. The population in this study were class X students of SMA Negeri 2 Manokwari Science and research samples used were students of class X IPA 1 and consisted of 36 students and students of class X IPA 2 consisting of 25 students. Based on statistical test data using analysis of variance with the help of SPSS 23, the significant value obtained for the learning model was 0.582> = 0.05, for learning activities 0.027 <= 0.05 and the interaction between learning models with learning activities on learning outcomes 0.669> = 0.05. The conclusions of this study are (i) There is no significant difference in the periodic system learning outcomes using the Problem Based Learning (PBL) and Team Assisted Individualization (TAI) learning models; (ii) There are significant differences in the learning activities of students in the elemental periodic system material for students who have active learning activities with inactive learning activities; (iii) There is no interaction between the learning model and learning activities on the periodic learning outcomes of elements. Keywords: Problem Based Learning (PBL) learning model, Team Assisted Individualization (TAI) learning model, learning activities, learning outcomes